Nasal vein occlusion after COVID-19: A case report - Yusuf Z Güven; Turan Akbalık; Fahrettin Akay (Indian Journal of Ophthalmology, 2022)
To present a case of nasal vein occlusion that has not been reported after the coronavirus disease 2019 (Covid-19) pandemic. A 53-year-old patient reported a complaint of floaters after a recent severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection. His best corrected visual acuity (BCVA) was 20/20 for both the eyes. On examination, a flame-shaped hemorrhage was observed in the left eye around the infero-nasal area adjacent to the optic disc. Temporal branch vein occlusion has been widely reported in association with SARS-CoV-2 infection. We emphasize that nasal vein occlusions triggered by Covid-19, which do not cause vision loss, should also be considered.